Staying out of trouble in pediatric orthopaedics - Skaggs, David L. (Wolters Kluwer, 2021)
"Filled with pearls and wisdom from experts in the field, Staying Out of Trouble in Pediatric Orthopaedics, 2nd Edition, is a concise, easy-to-read guide to managing difficult orthopaedic problems in children. This high-yield, highly illustrated reference provides practical advice on how to deal with commonly seen issues as well as those that are less common but that pose grave threats to the patient. Focusing on preventing problems and avoiding serious complications and prepared by editors, authors, and gurus with more than 1000 years of combined experience in pediatric orthopaedics, this title is an invaluable resource for pediatric orthopaedic surgery fellows and all orthopaedists who care for children"--